Review of recently reported Ricin detection techniques focusing on combined immunoassay detection with abrin and saxitoxin in human plasma - Kang, Seungmin; Kim, Seonhee; Churchill, David G.; Ku, Kang; Jang, Yoonjeong (Seonjin gukbang yeongu (Online), 2023)
Increasing non-traditional threats from biological or chemical weapons, the Organisation for the Prohibition of Chemical Weapons (OPCW) have tried to perform the preliminary analysis of biotoxin sample to standardize analysis methods and strengthen analytical capabilities among OPCW member countries. With the changes of new analysis, ROK CBRN Defense Research Institute (CDRI) established enzyme-linked immunosorbent assay (ELISA) and cytotoxicity analysis methods for ricin, abrin, and saxitoxin through the OPCW exercise on Biotoxin sample analysis. Thus, this study aims to established analytical methods (ELISA and cytotoxicity analysis) for the biological toxins called ricin, abrin and saxitoxin according to recent OPCW Biotoxin detection exercise. In particular, to refine practical and effective methods of biological analysis, we reviewed recent research on scientific analysis of ricin as a potential bioterror weapon, letter with ricin sent in White House, and suggested future agendas for preparedness testing.